Comparison of Two Ferredoxins from Rhodospirillum rubrum as Electron Carriers for the Native Nitrogenase - Yoch, Duane C. (1975)
In coupling the reducing power of illuminated chloroplasts to the nitrogenase from photosynthetically grown Rhodospirillum rubrum cells, one of the native ferredoxins. FdI, was found to be three times more effective than FdII.